A Study of Important Website Design Criteria to Achieve Customer Satisfaction of University Students Browsing China Tour Agency Websites - Lu, Xiaotong (2013)
The purpose of this study is to identify important website design criteria that will impact students’ satisfaction of tour agencies’ websites for e-tourism in China. As the e-tourism market is developing very fast in the world as well as in China, and the trend of the combination of tourism and e-commence is not unstopped, the development of the tour agencies’ website becomes more important for the tour agencies to attract more customers for increasing e-tourism. As web quality of the tour agencies’ websites is affecting the performance of the tour agencies in China, how to develop the websites of the tour agencies to focus on. In this study, four factors will be chosen as indicator to test customer satisfaction, which are quality of information, website navigability, website confidence/trust, and website innovativeness. In this research, SPSS 20.0 is used to analyze the data from responses of university students collected through a questionnaire. The analysis methods include descriptive analysis as well as reliability and validity, correlation, and regression test. In addition, SmartPLS is also used to further analyze the data. According to the data analysis, website confidence/trust has the most influence on customer satisfaction. Thus, tour agencies can improve their websites to meet university students’ needs and then improve customer satisfaction in order to attract younger and well educated customers, and improve company performance.